Las mnemotecnias HEITSCHAFTUNGKEIT y MENTUMNISEM en la retención de los artículos determinados “die” y “das” del idioma alemán - Cotrina Lázaro, Marcia Ximena (2019)
Many articles published by the Ministry of Education and studies based on statistical figures show the low competence of Peruvian students in foreign languages. In view of this situation and to improve the teaching of the language, the application of mnemonics is proposed as a methodological solution, which makes the German language easier to acquire and / or retain. Due to the complexity of the grammar, it hinders their learning, by the same fact of following patterns that differentiates it from the other languages that make it a little difficult to retain German grammar. For this reason, different innovative techniques are included that allow the easy learning of the language. The present investigation titled: The mnemonics "HEITSCHAFTUNGKEIT" and "MENTUMNISEM" in the retention of the German articles "die" and "das", had as main objective to determine the influence of the application of these mnemonics in the students who attend the second year high school of the San Juan Educational Institution, taking a total of 26 students as a sample. At the same time, this research seeks to make the retention of certain articles of the German language more dynamic and practical, through the use of mnemonics that facilitate the learning of this language. To achieve this goal, six learning sessions including pretest and posttest were applied. As a result of the application of the mentioned mnemotechnics, the following information was obtained: In the posttest, the experimental group achieved a satisfactory result; where 100% of them presented a performance at a good level with notes between 15 and 20; unlike the pretest, where 84% presented a bad performance with grades between 0 and 10, while 16% of them presented a performance at a regular level with grades between 11 and 14.